Validation of Activity Tracking Procedures in Elderly Patients after Operative Treatment of Proximal Femur Fractures. (19th June 2018) - Schmal, Hagen; Holsgaard-Larsen, Anders; Izadpanah, Kaywan; Brønd, Jan Christian; Madsen, Carsten Fladmose; Lauritsen, Jens
Abstract : Background . Early postoperative physical activity in elderly patients suffering from proximal femoral fractures may reduce mortality. We hypothesized that activity trackers can reliably and objectively monitor the in-hospital mobilization, correlating with functional independence and quality of life. Methods . Three different tracker types (Fitbit™ flex, Misfit™ Shine, and Axivity AX3) at three locations (wrist, ankle, and femur) recorded steps and signal vector magnitudes (SVM) in 22 patients. They were81 ± 8 years old, were equally distributed between the sexes, and had an ASA score of2.5 ± 0.6 . Single protocoled activity events (n = 191 ) were clinically categorized into 4 levels and correlated with the monitored signals. Additionally, 2 ± 1 and8 ± 3 days after the operation, the EuroQol-5D and the Barthel-20 index supplemented this data. Results . All measurements at the wrist (Fitbit, Misfit) resulted in unacceptable accuracy; however, sensitivity and specificity reached around 90% using the Misfit at the ankle. Applying this combination, the correlation between real and measured steps (R 2 = 0.99) and the category discrimination were statistically significant (p < 0.002 ). A discriminant analysis featured the calculation of four activity levels based on SVM measurements using the Axivity tracker at the femur. A cluster analysis showed a 100% agreement between the clinically observed and the calculated activity levels. The amount of active minutes or periods and both the EuroQol-5D and the Barthel-20 indices significantly increased between the analyzed time points after the operation. However, only the Barthel-20 was associated with the measured activity levels (p < 0.01 ). Conclusion . The Misfit and the Axivity trackers can reliably monitor activity in elderly patients after operative treatment of proximal femur fractures. However, the wear location is decisive. Objectively measured activity correlated with functional independence and quality of life.